Green tea extract and the risk of drug-induced liver injury. (December 2014) - Teschke, Rolf; Zhang, Li; Melzer, Lena; Schulze, Johannes; Eickhoff, Axel
<x xml:space="preserve">Abstract</x> Introduction: Catechins of green tea extract (GTE) have been associated with the rare risk of hepatotoxicity in a few individuals. As GTE were coadministered with synthetic drugs in some hepatotoxicity cases, uncertainty emerged whether GTE are a risk factor of drug-induced liver injury (DILI). Areas covered: Case reports of liver injury by GTE and related review articles to assess the drugs that were coadministered with GTE were reviewed. The analysis included the question whether a formal causality of liver injury had confidently been attributed to GTE, the comedicated drug(s) or both. To elucidate possible metabolic interactions, GTE and their catechins were analyzed regarding their affinity to various CYP isoforms. Expert opinion: The authors conclude that the published hepatotoxicity case reports in connection with the use of GTE provide no clinical evidence that GTE may increase the risk of DILI by drugs that had been comedicated in only few cases. Although partial inhibition of human hepatic and intestinal microsomal CYP2C8, CYP2B6, CYP3A4, CYP2D6 and CYP2C19 by GTE catechins was observed in vitro, a clinical study of drug bioavailability attributed a small risk of increased plasma drug levels only for substrates metabolized by CYP3A4, lacking clinical relevance.